Implementation of Syari'ah Pawning at Perum Syari'ah Pawnshops Perspective of the Fatwa of the National Syari'ah Council Number 25/DSN-MUI/III/2002: A Case Study at the Sharia Pawnshop Iringmulyo 15.A East Metro - Ambariyani; Damayanti , Wiwik; Nurhasanah , Siti (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Islam commands that we always help each other in all our actions, including in carrying out economic transactions, one of which is giving loans. Therefore, the creditor is allowed to request an item from the debtor (the person who is given a loan) to be used as collateral for what has been lent to him. This is done by several pawnshops in cities in Indonesia. Thus, the purpose and objective of the research is how the implementation of pawning, especially sharia, is carried out on the basis of conformity with the Fatwa of the National Sharia Council Number 25/DSN-MUI/III/2002. This type of research is a field qualitative research and this research uses a qualitative descriptive research approach. Sources of data used are primary and secondary data sources. Data collection techniques using observation, interviews and documentation with data triangulation method. The results of the study show that the implementation of sharia conformity pawning is an effort to control the operations of sharia financial institutions, especially sharia pawnshops. The National Sharia Council Fatwa No.25/DSN-MUI/III/2002 stipulated by the Indonesian Ulema Council made a provision that the amount of maintenance and storage costs for marhun should not be determined based on the amount of the loan. This is the fault of the rules made by the National Sharia Council Fatwa No.25/DSN-MUI/III/2002 Where the determination of maintenance costs is adjusted based on the amount of the loan, not the estimated price of the goods